Supplier codes of conduct: Acting responsibly in global supply chains - Kärppälä, Eva (My University, 2014)
Nowadays the Western companies are considered responsible for the social and environmental issues in their whole supply chains. To influence the practices of their suppliers the Western companies have created suppliers codes of conduct (SCCs) which express their requirements. Suppliers’ compliance with the SCCs is checked through audits. The purpose of this thesis is to analyze SCCs as a means for Western companies to ensure socially and environmentally responsible actions in their global supply chains, and the sub-objectives are to find out 1) how well do the SCCs and their auditing work at suppliers’ production sites and 2) how can possible problems related to SCCs and their auditing be solved. This is a qualitative research carried out in the form of a case study with two case companies. In this study both primary and secondary data is used. The primary data is collected in the form of interviews of the case company representatives and three external experts. Based on a theoretical framework of previous research in the fields of corporate social responsibility and supply chain management, a model with eleven factors, which influence the success of SCC implementation and the auditing of SCC –implementation, is drafted. Also several different best-practices to help to solve and avoid possible problems related to SCC -implementation and auditing have been identified from previous research. Based on the findings of this study the theoretical model has been updated adding two new influential factors. It seems that how well the SCC and its auditing work at suppliers’ production sites depends on the joint effect of thirteen influential factors: buyer’s purchasing policy, supplier’s motivation, buyer’s commitment, the solving of agency problems, the contents of the SCC, supplier’s role and the buyer-supplier –relationship, complexity of supply chain, the limitations of the smaller buyers, cooperation through a business association or multi-stakeholder system, the role of supplier’s employees, SCC –related communication and supplier’s understanding, cheating in audits and the auditors. The possible problems related to SCCs and their auditing can be solved by adopting best-practices. Nine of the theoretical best-practices stand out from the findings of this study: 1) two-way communication and collecting feedback from suppliers, 2) the philosophy of continuous improvement, 3) long-term business relationships with the supplier, 4) informing the supplier about the advantages of SCC –compliance, 5) rewarding code-compliant suppliers, 6) building collaborative, good buyer-supplier relationships, 7) supporting and advising the supplier, 8) joining a business association or multi-stakeholder system and 9) interviewing supplier’s employees as a part of the audits.